2018
DOI: 10.1049/mnl.2018.5083
|View full text |Cite
|
Sign up to set email alerts
|

GaN LEDs fabricated using SF 6 plasma RIE

Abstract: In this work, the authors report a cost-effective fabrication method for making gallium nitride (GaN) light emitting diode (LED) arrays using SF 6 plasma in a conventional reactive-ion etching (RIE) system. The etch rates for GaN were investigated with different radio-frequency power and carrier substrates. The surface roughness due to the etching was also determined for the various recipes used. The optical intensity and the temperature change during operation of the fabricated LED's were investigated. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…This was done to avoid the usage of more commonly used, but corrosive, chloride- and bromide-based gases in the fabrication process, which may damage the established Cr masks. Moreover, to employ such highly toxic gases, a costly reactive chamber with specific filtration system is required, not to mention a high risk of continuously damaging the vacuum systems …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done to avoid the usage of more commonly used, but corrosive, chloride- and bromide-based gases in the fabrication process, which may damage the established Cr masks. Moreover, to employ such highly toxic gases, a costly reactive chamber with specific filtration system is required, not to mention a high risk of continuously damaging the vacuum systems …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, to employ such highly toxic gases, a costly reactive chamber with specific filtration system is required, not to mention a high risk of continuously damaging the vacuum systems. 36 The detailed mechanism of the SF 6 /H 2 dry etching has not been to date fully understood. However, some previous studies 29,37−40 showed that GaN reacts with SF 6 /H 2 and produces volatile compounds of NF 3 (boiling point T B = −129 °C) and NH 3 (T B = −33 °C), as well as nonvolatile GaF 3 (T B ≈ 1000 °C) , which would be removed by physical ion bombardment of hydrogen and SF x .…”
Section: Methodsmentioning
confidence: 99%